Detached House - Hajiyev, Mustafa (Vysoké učení technické v Brně. Fakulta stavební, 2020)
The subject of this bachelor thesis is the about the family residence. The detached house is located in Brno-Královo Pole, in cadastral area Poděbradova. The family house is located on a relatively flat plot and is situated on the north side. The house has two floors, with a balcony on the second floor and flat roof. On the east side there is a storage. The whole family building the residence is made of concrete slabs, with the main focus on Steico building materials. All insulation materials are from Isover. Project documentation was performed in Autocad computer software.
Rodinný dům
Keywords: Low energy house; two-floor family house; detached house; concrete skeleton; strip foundation; connecting beam